Computer and Information Science 2011 - Lee, Roger (2011)
The series "Studies in Computational Intelligence" (SCI) publishes new developments and advances in the various areas of computational intelligence quickly and with a high quality. The intent is to cover the theory, applications, and design methods of computational intelligence, as embedded in the fields of engineering, computer science, physics and life science, as well as the methodologies behind them. The series contains monographs, lecture notes and edited volumes in computational intelligence spanning the areas of neural networks, connectionist systems, genetic algorithms, evolutionary computation, artificial intelligence, cellular automata, self-organizing systems, soft computing, fuzzy systems, and hybrid intelligent systems. Critical to both contributors and readers are the short publication time and world-wide distribution - this permits a rapid and broad dissemination of research results. The purpose of the 10th IEEE/ACIS International Conference on Computer and Information Science (ICIS 2011) was held on May16-18, 2011 in Sanya, Hainan Island, China is to bring together scientist, engineers, computer users, students to share their experiences and exchange new ideas, and research results about all aspects (theory, applications and tools) of computer and information science, and to discuss the practical challenges encountered along the way and the solutions adopted to solve them. The conference organizers selected the best 20 papers from those papers accepted for presentation at the conference in order to publish them in this volume.á The papers were chosen based on review scores submitted by members of the program committee, and underwent further rigorous rounds of review.
Appling Bounded Model Checking to Verifying Web Navigation Model -- A Metri-Based Approach for Anti-Pattern Detection in UML Designs -- A Novel Feature Extraction for Facial Expresion Recognition Via Combining the Curvelet and LDP -- Constructing Maximum-Lifetime Data Gathering Tree without Data Aggregation for Sensor Networks -- An Empirical Study of Programming Performance Based on Keystroke Characteristics -- A Theory of Planned Behavior Perspective on Blog Service Switching -- User Contribution and IT-Enabled Features of Online Review Platforms: A Preliminary Study -- Implementation and Performance Analysis of Fuzzy Replica Replacement Algorithm in Data Grid -- Integrating Business Process Analysis and Complex Event Processing -- 3D NAT Scheme for Realizing Seamless-End-to-End Connectivity and Addressing Multilevel Nested Networking Address Translation Issues -- Maximizing coverage degree based on event patterns in wireless sensor net-works -- Formal Specification and Implementation of Priority Queue with Starvation Handling -- Brain Functional Network for Chewing of Gum -- Effects of Value-based Mechanism in Online Advertisement Auction -- Research on Dynamic Optimized Approach of Value Chain in Tourist Destinations -- Analysis and Quantitative Calculation on Switching Costs: Taking 2002-2006 China Wireless Telecommunications Market as an Example -- An Empirical Study of Network Topology Inference -- Computer Network Reverse Engineering -- CUDA-based Genetic Algorithm on Traveling Salesman Problem -- Design and Implementation of Sensor Framework for U-Healthcare Services.
Keywords: Engineering; Artificial intelligence; Artificial Intelligence (incl. Robotics).; COMPUTATIONAL INTELIGENCE